2009
DOI: 10.1039/b818339b
|View full text |Cite
|
Sign up to set email alerts
|

Diversity oriented syntheses of fused pyrimidines designed as potential antifolates

Abstract: Diversity oriented syntheses of some furo[2,3-d]pyrimidines and pyrrolo[2,3-d]pyrimidines related to folate, guanine, and diaminopyrimidine-containing drugs have been developed for the preparation of potential anti-infective and anticancer compounds. Amide couplings and Suzuki couplings on the basic heterocyclic templates were used, in the latter case yields being especially high using aromatic trifluoroborates as the coupling partner. A new ring synthesis of 6-aryl-substituted deazaguanines bearing 2-alkylthi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 69 publications
1
28
0
Order By: Relevance
“…27,28 Assays for activity against T. brucei were carried out using established methods at the laboratories in Strathclyde and Glasgow Universities. 29 Compound 20 is typical of an antibacterial and antifungal minor groove binder with an MIC vs. S. Aureus 4.3 μM, vs. A. niger 4.3 μM. However, this compound was found to be inactive against T. brucei.…”
Section: Mgbs With Anti-parasitic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 Assays for activity against T. brucei were carried out using established methods at the laboratories in Strathclyde and Glasgow Universities. 29 Compound 20 is typical of an antibacterial and antifungal minor groove binder with an MIC vs. S. Aureus 4.3 μM, vs. A. niger 4.3 μM. However, this compound was found to be inactive against T. brucei.…”
Section: Mgbs With Anti-parasitic Activitymentioning
confidence: 99%
“…This was demonstrated in a number of publications. 26,29,30 These were thiazole-containing compounds, activity was found against Trypanosoma brucei (see Tables 2 and 3).…”
Section: Mgbs With Anti-parasitic Activitymentioning
confidence: 99%
“…Many compounds demonstrated very promising activity in vitro. Diversity-oriented synthesis was used in the synthesis of fused pyrimidine analogues (Gibson et al, 2009). The compounds were tested against pteridine reductases from protozoan parasites and several were found to be active.…”
Section: Medicinal Chemistrymentioning
confidence: 99%
“…With emphasis on diversity oriented synthesis in our own studies, we have identified active compounds with respect to GTP cyclohydrolase 1, 2 dihydropterin diphosphokinase, 3 dihydrofolate reductase, 4 pteridine reductase 1 5 and nitric oxide synthase. 6 Several of these targets are significant clinically and the optimisation of activity requires the availability of more diverse libraries within the same basic structural skeleton.…”
Section: Introductionmentioning
confidence: 99%
“…A significant exception is that when certain Michael acceptors are used, C5 substitution occurs in reduced yield 8 and this chemistry has been developed to provide compounds with significant activity against Trypanosoma brucei. 5 A further example of a successful C5 substitution of a 2-alkylthiopyrimidine is found in nucleoside analogue synthesis and involves Vilsmeier formylation. 9 In contrast, halogen electrophiles substitute 2-alkylthiopyrimidines in high yield and provide suitable precursors for C5 carbon substitution.…”
Section: Introductionmentioning
confidence: 99%